Moral Design and Green Technology - Bart Wernaart; Gerard Schouten (Brill | Wageningen Academic, 2025)
Welcome to the Anthropocene, the era in which humans have put a tangible mark on our planet. But also the era in which humans and technology have the potential to shape the necessary transitions towards a sustainable world. Technology and nature are often considered as two opposing phenomena. However, they are increasingly intertwined, for better or worse. In this book, we explore how technology and nature relate to one another in the moral design of new, green technology. This book is relevant for IT and engineering professionals, business leaders and policy makers with (green) innovation in their portfolios and students of (applied) science who are interested in either sustainable and green design of technology or in the application of technology – with an emphasis on AI and IT – to create a greener, more sustainable world. The chapters have been written by experts and leading researchers in an attractive, accessible, and practical writing style. Each chapter offers colourful examples and challenges the reader to critically think through moral decision-making and the design of innovations considering our planet's perspective. This is a conceptual change in values. Nature should not be considered as a resource: it is the fabric of life that makes our own existence possible.